How different emotion processes influence disordered eating?: the distinct effect of body image-related cognitive fusion and body appreciation - Bento, Sofia Santos (2016)
The impact of body image-related variables in eating psychopathology may be influenced by different emotion regulation processes. This study aims to clarify the distinct effect of cognitive fusion and body appreciation, in the relationship between body image discrepancy and disordered eating, while controlling the effect of BMI in a sample of 369 women. The model explained 67% of eating psychopathology’s variance and results, tested via path analysis, indicated that women who perceived their body as significantly discrepant from the social and culturally ideal thin figure, have a greater tendency to engage in disordered eating behaviours. This association is partially carried by distinct emotion regulation processes, namely body image-related cognitive fusion and body appreciation. Furthermore, results offer relevant contributions for research and clinical practice in the field of body image and eating difficulties providing empirical support for targeting cognitive defusion and self-compassionate attitude as protective emotion regulation strategies against eating psychopathology.